Responsive Laws to Support The Tourism Policy Based Local Pluralism - Isharyanto Isharyanto; Maria Madalina; Ayyub Torry Satryo Kusumo (Alliance of Health Activists (AloHA), 2020)
Local pluralism is a driver of tourism policy, with an emphasis on changing the quality of life. Decentralization gives legitimacy to each region to produce or produce various policies that are in accordance with regional needs, including in the field of tourism. In this regard, each region besides having the potential for tourism that is not the same, also competes to optimize local local potential. Considering the implementation of government affairs in the region, including tourism, requires an appropriate legal foundation, an analysis of the relevant laws and regulations is needed. This study confirms that Bali, Surakarta, and Batu endeavor culture as a form of local pluralism to sustain the local tourism policies. However, the three objects of observation in this study have differences in institutionalizing local pluralism in the tourism policy. Regional Regulations in Bali need to be revised, while conversely, in Surakarta and Batu need to make Regional Regulations on Tourism Based on Local Pluralism. Keywords: tourism; local pluralism; culture; tourism policy